Effectiveness of nonpharmacological interventions for reducing postpartum fatigue: a meta-analysis - Jialu Qian; Shiwen Sun; Lu Liu; Xiaoyan Yu (BMC, 2021)
Abstract Background Postpartum fatigue is the most common issue among postnatal women and it could not only seriously affect the health of mothers but also bring about adverse impacts on their offspring. This meta-analysis aims to synthesize nonpharmacological evidence and evaluate the effectiveness of interventions for reducing postpartum fatigue among puerperae. Methods The Cochrane Library, PubMed, Embase, Web of Science, PsycINFO, CINAHL and ProQuest databases were searched for papers published from inception until June 2021. Grey literature was searched using OpenGrey. Randomized controlled trials (RCTs) or controlled clinical trials (CCTs) evaluating nonpharmacological interventions conducted during 0 ~ 78 weeks postpartum for fatigue reduction were eligible for inclusion. The methodological quality of the included studies was independently assessed by two reviewers using the Cochrane risk-of-bias tool and the risk of bias in nonrandomized studies of interventions. Cohen's kappa coefficient was used to measure inter-rater agreement. The meta-analysis was conducted using Review Manager 5.3. Results Seventeen published clinical trials matched the eligibility criteria and ten studies involving 1194 participants were included in this meta-analysis. The intervention start time varied from immediately postpartum care to 1 year after delivery, and duration ranged from 1 day to 3 months. The results revealed that exercise (SMD = − 1.74, 95% CI = -2.61 to − 0.88) and drinking tea (MD = − 3.12, 95% CI = -5.44 to − 0.80) resulted in significant improvements in women's postpartum fatigue at postintervention. Drinking tea may have beneficial effects on depression (MD = − 2.89, 95% CI = -4.30 to − 1.49). Positive effects of psychoeducational interventions on postpartum fatigue or depression were not observed. Physical therapies including mother-infant skin-to-skin contact, taking warm showers and breathing lavender oil aroma were used for reducing postpartum fatigue. No significant risk of publication bias was found. Small number of included studies and sample sizes, not time-matched conditions of control groups, high heterogeneity and the risk of bias within the included studies were the main limitations of our review. Conclusions This review provides evidence that exercise and drinking tea may be effective nonpharmacological interventions for relieving postpartum fatigue. More effective and targeted exercise programs need to be further studied. Rigorous RCTs of drinking tea are needed. Caution is required when interpreting the findings due to the limitations of our study. Further studies are still needed to validate our findings and increase confidence in the results.